Temperature and concentration dependence of density of model liquid foods - Darros-Barbosa, R.; Balaban, M. O.; Teixeira, A. A. (Marcel Dekker Inc, 2003)
Density of binary solutions and combinations of sucrose, glucose, fructose, citric acid, malic acid, pectin, and inorganic salts were measured with an oscillating tube density meter in the temperature range from 10degrees to 60degreesC, at varying concentrations. Density can be predicted with accuracy better than 5 x 10(-5) g cm(-3) using predictive equations obtained by fitting the experimental data. Available literature values agreed well with experimental data. Relations for the excess molar volume of these solutions were derived in terms of mole fraction and temperature. A thermodynamic model for the volumetric analysis of multicomponent aqueous solutions containing electrolyte and non-electrolyte compounds was also proposed. These models can be used for prediction of density of liquid food systems, specially fruit juices and beverages, based on composition and temperature, with high accuracy and without elaborate experimental work.
Keywords: density; specific volume; oscillating tube; multicomponent aqueous solutions; predictive model; excess functions